PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, INTENSITAS ASET TETAP, INTENSITAS PERSEDIAAN, DAN KOMISARIS INDEPENDEN TERHADAP EFFECTIVE TAX RATE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - BR Panggabean, Risa Mewanda; Zirman, Zirman; Rofika, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aimed to determine the influence of size, leverage, profitability, capital intensity ratio, inventory intensity ratio and independent commissioner ratio to the Effective tax rate (Empirical Study on Manufacturing Companies listed in Indonesia Stock Exchange 2014-2016). This study using purposive sampling technique in which study took company file manufacture listed on the Stock Exchange in the period 2014-2016. The population is research were 144 companies with a selected sample of the sample is based on researchcriteria as many as 171 companies sampled. Multiple regresion is used to test the hypothesis. After it was tested by using SPSS version 22. The results of this study declare that the size has a impact on the effective tax rate at P<0,05 (P=0,010), leverage has a impact on the effective tax rate at P<0,05 (P=0,002), and capital intensity ratio has a impact on the effective tax rate at P<0,05 (P=0,049). While profitability has doesn’t impact on the effective tax rate at P<0,05 (P=0,948) , inventory intensity ratio has doesn’t impact on the effective tax rate at P<0,05 (P=0,197) , and independent commissioner has doesn’t impact on the effective tax rate at P<0,05 (P=0,658). Adjusted R Square shows the value of 0,123. It means that 12,3% change in the effective tax rate is affected by the determinant variables in the model. The small coefficient of determination in this study is caused by the independent variables tested that have a little relationship to the dependent variable.Keywords: Effective Tax Rate, Corporate Size, Leverage, Profitability, Intensity of Fixed Assets, Inventory Intensity Ratio and Independent Commissioner